SROI Self-assessment tool (SROI Network, 2016)
The online self assessment tool was created by the SROI Network in col laboration with Hall Aitken to help users judge how well their evaluat ion practices adhere to principles of best practice. The tool is compr ised of a seven stage questionnaire, showing results as a spider chart illustrating areas of strength and areas for improvement. The questio nnaire itself is structured around the seven principles of SROI. These principles include ‘involve stakeholders’, ‘be transparent’ and ‘do n ot overclaim’, and together make up the core framework around which SR OI is based. Users receive a score for each principle, and an overall average, giving them an idea of to what extent they have successfully applied the principles. High scoring users can then use their score to guide them towards applying for assurance and accreditation. The tool provides guidance, support and more advice to people who want to impr ove the way in which their organisation measures their social value an d assesses their service delivery but don’t know where to start.